Recoleccion de germoplasma de Phaseolus (frijol) en el Occidente de Guatemala - Debouck, Daniel G.; Soto D., J.J. (1988)
During a 3-wk. trip to western Guatemala to collect bean germplasm, 88 seed samples were collected, representing 10 species in different forms. The germplasm involves 3 cultivated species (coccineus, polyanthus, and vulgaris), the ancestral forms of coccineus, lunatus, and polyanthus, and 3 wild species (including P. macrolepis and P. xanthotrichus). (AS-CIAT)